Brand service quality as predictor of brand loyalty: A study of the Nigerian telecommunication industry - Ekakitie-Emonena, Sunny (Edelweiss Applied Science and Technology, 2025)
The study focused to assess the predictability of certain factors of brand service quality as it relates to brand loyalty of telecommunication subscribers in the Nigerian telecom industry. The empirical analyses was based on MTN Nigeria as a dominant player in the sector. The factors of superior service delivery, unforgettable services received, excellent service experience, good feeling at service consumption and consistency in service quality delivery were tested as drivers against brand loyalty. Survey research vide a structured questionnaire instrument containing a 5- scale likert type questions with 15-items was designed and administered to 565 users of MTN brand of service. Multiple regression statistics (SPSS Vrs 32) was used for analyses at 5% level of significance. Of the five (5) hypotheses tested, only Ho2 (B = .038, t = 1.074, p = .283) & Ho5 (B = -0.042, t = -1.151, p = .250) were accepted as both factors were found insignificant drivers, with Ho5 posting a negative association with brand loyalty. All other three hypotheses (Ho: BSQ1, BSQ3 & BSQ4); (B=.118, t = 3.480, p = .001), (B = .252, t = 6.722, p = .000), and (B = .131, t = 3.858, p = .000) respectively were rejected with significant values. This implies that the null hypotheses 1, 3 & 4 are strong drivers of loyalty in MTN brand of service. Recommendations are to the effect that Brand managers in MTN Nigeria should sustain the factors that are significant and engage a policy adjustment to turn around defects in unforgettable service received and service quality delivery as revealed. This outcome is also in assonance with public observation generally.